Towards a comprehensive picture of C-to-U RNA editing sites in angiosperm mitochondria - Edera, Alejandro (2018)
Key message: Our understanding of the dynamic and evolution of RNA editing in angiosperms is in part limited by the few editing sites identified to date. This study identified 10,217 editing sites from 17 diverse angiosperms. Our analyses confirmed the universality of certain features of RNA editing, and offer new evidence behind the loss of editing sites in angiosperms. Abstract: RNA editing is a post-transcriptional process that substitutes cytidines (C) for uridines (U) in organellar transcripts of angiosperms. These substitutions mostly take place in mitochondrial messenger RNAs at specific positions called editing sites. By means of publicly available RNA-seq data, this study identified 10,217 editing sites in mitochondrial protein-coding genes of 17 diverse angiosperms. Even though other types of mismatches were also identified, we did not find evidence of non-canonical editing processes. The results showed an uneven distribution of editing sites among species, genes, and codon positions. The analyses revealed that editing sites were conserved across angiosperms but there were some species-specific sites. Non-synonymous editing sites were particularly highly conserved (~ 80%) across the plant species and were efficiently edited (80% editing extent). In contrast, editing sites at third codon positions were poorly conserved (~ 30%) and only partially edited (~ 40% editing extent). We found that the loss of editing sites along angiosperm evolution is mainly occurring by replacing editing sites with thymidines, instead of a degradation of the editing recognition motif around editing sites. Consecutive and highly conserved editing sites had been replaced by thymidines as result of retroprocessing, by which edited transcripts are reverse transcribed to cDNA and then integrated into the genome by homologous recombination. This phenomenon was more pronounced in eudicots, and in the gene cox1. These results suggest that retroprocessing is a widespread driving force underlying the loss of editing sites in angiosperm mitochondria.